Childcare for Children under Three Years of Age from Mothers' Point of View within the International Context - Lucie Grůzová; Zora Syslová (Charles University, 2020)
The present study brings a discussion on institutional care and education for children under three into the professional discourse. In the introduction, the authors introduce the historical context of care for children under the age of three in the Czech Republic and compare it with the situation elsewhere in the European Union. The core of the article was mothers' viewpoint on facilities for children under three in the Czech Republic. A qualitative probe answers the question, "How do mothers perceive facilities for children under three years of age?" In-depth interviews revealed that the mothers who were addressed have a wide range of motives for deciding to place a child under three years of age in institutional care. Ultimately, however, they seek to satisfy the needs of their child. The situation of the sample that was monitored is in many respects comparable to foreign studies, even though the Czech situation regarding these services has specific features because of its historical development. Keywords: early childhood education, day care institutions in the Czech Republic, state family policy, mothers